CITRA PEREMPUAN PADA PERILAKU MEROKOK - Yensin Tria; Yuliana Tapparan Turu’ Allo (CV. ADIBA AISHA AMIRA, 2025)
The phenomenon of female smokers in Indonesia has become an increasingly complex social issue in line with cultural changes and globalization. Smoking behavior among women is no longer simply viewed as a habit that negatively impacts health, but is also related to self-image, social identity, and cultural dynamics. This study aims to examine how women's image is shaped through smoking behavior, taking into account internal factors, the environment, social stigma, and changes in cultural perceptions. The research method used a qualitative approach with a literature review of various journal sources, theses, and recent research results. The results of the study indicate that internal factors such as emotional drives, psychological needs, and self-identity negotiation play a significant role in encouraging women to smoke. Meanwhile, environmental factors such as family, peers, and media representation also strengthen or weaken this behavior. Although the social stigma against female smokers remains strong, especially in traditional societies, modernization has opened up space for more diverse self-image negotiations. This phenomenon demonstrates that female smokers are in an ambivalent position: on the one hand, they are considered deviant, on the other, they are seen as a symbol of freedom and gender equality. This study emphasizes that the issue of female smokers needs to be viewed not only from a health perspective, but also from a social, cultural, and psychological perspective.